2012
DOI: 10.1590/s1516-35982012000800011
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the protein level and addition of oil in diets for finishing pugs under different temperatures

Abstract: -The objective of this study was to evaluate the effect of reducing the crude protein (CP) with the use of amino acids in diets with the same amount of calories anddifferent levels of soybean oil (SO) for finishing pigs kept in two different ambient temperatures. A total of 120 barrows (initial weight of 68.0±1.9 kg) were utilized for the experiment. The design was of randomized blocks in a 2 × 3 × 2 factorial arrangement (two levels of CP, 16.2 and 13.7%; three levels of SO, 1.5; 3.0 and 4.5%; and two ambient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
1
0
2
Order By: Relevance
“…Because feed intake at high ambient temperatures is limited by the capacity of the animal to dissipate heat, the greater feed intake of HF/LP pigs might be explained by the lower thermic effect of the diet. These results are consistent with previous literature (Spencer et al, 2005;Rodrigues et al, 2012) that similarly reported a greater performance of heat-stressed finishing pigs fed high-fat/low-CP diets.…”
Section: Effect Of Hf/low-crude Protein Sequential Feeding On Pig Performance and Body Compositionsupporting
confidence: 93%
“…Because feed intake at high ambient temperatures is limited by the capacity of the animal to dissipate heat, the greater feed intake of HF/LP pigs might be explained by the lower thermic effect of the diet. These results are consistent with previous literature (Spencer et al, 2005;Rodrigues et al, 2012) that similarly reported a greater performance of heat-stressed finishing pigs fed high-fat/low-CP diets.…”
Section: Effect Of Hf/low-crude Protein Sequential Feeding On Pig Performance and Body Compositionsupporting
confidence: 93%
“…As rações experimentais (Tabela 1) foram formuladas para atender as recomendações nutricionais propostas por Rostagno et al (2005), com exceção da proteína bruta (PB), que foi reduzida de acordo com os tratamentos (20,5; 19,4; 18,3 e 17,2%) e realizada a devida suplementação com aminoácidos sintéticos. Para tanto, foram realizadas as análises de PB, do milho e farelo de soja, no Laboratório de Nutrição Animal da UNIOESTE.…”
Section: Methodsunclassified
“…The biological influence of heat stress is impacted by duration of exposure to extreme temperatures (Renaudeau et al, 2007), night cooling (Xin and DeShazer, 1991;Patience et al, 2005), relative humidity (Huynh et al, 2005), diet composition (Jørgensen et al, 1996;Kerr et al, 2003), and genetics (Brown-Brandl et al, 2001;Sutherland et al, 2006), among others. In particular, ME content (Baldwin and Sainz, 1995;Rodrigues et al, 2012), protein and AA balance (Kerr et al, 2003;Spencer et al, 2005;Wolp et al, 2012), dietary additives (Zier-Rush et al, 2014) ,and mineral concentrations (Haydon et al, 1990;Kim et al, 2009) all affect responses to heat stress. To understand the relationships among variables, a mixed-effect linear model of absolute intake was also derived from the data set.…”
Section: Model Improvementmentioning
confidence: 99%